(untitled) - Thornbury, Scott (Harlow, 2007)
This book deal with the recent availability of computerised databases of words nad the developmentof new approaches to language teaching which are much more word centred such as lexical approach. The book includes a description of how words are learned, a guide to useful sources of vocabulary for classroom use, including coursebooks, corpora and dictionaries; approaches to presenting and consolidating vocabulary knowledge; ways of testing vocabulary. The book also has Task File of photocopiable training tasks
Keywords: English language,Vocabulary,Anh ngữ; Study and teaching,Foreign speakers,Dạy và học,Người nước ngoài